PENGARUH LATIHAN CONTROLLED SPEED POLYGON TERHADAPT DAYA TAHAN AEROBIK PADA TIM BOLA VOLI SMP NEGERI 10 PEKANBARU - Trysha Mutiarani Yonri; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to find out whether there was an effect of Controlled Speed Polygon exercise in endurance on volleyball team of SMPN 10 Pekanbaru, with the result that during the competition athletes always experience excessive fatigue. This research was experimental research, the population was volleyball players in SMPN 10 Pekanbaru, the data in this research were all populations which consists of 9 people. The instrument carried out in this research was a 1600 m run test, which aims to measure aerobic endurance. The data in this research was processed by using statistics, to test the normality by the lilliefors test at a significant level of 0.05. The hypothesis proposed, that there was an effect of Controlled Speed Polygon exercise in aerobic endurance. Based on the t-test analysis, Tvalue was 2,16 and Ttable was 1,860 which means Tvalue > Ttable. Based on statistical data analysis, Based on statistical data analysis, the mean of Pre-Test was 15.22 and the mean of post-test was 14.44, which means the data were normal. Therefore, it can be concluded that there was an effect of the Controlled Speed Polygon exercise in aerobic endurance on the volleyball team of SMPN 10 Pekanbaru.Key Words: Controlled Speed Polygon, Aerobic Endurance